2018
DOI: 10.1158/0008-5472.can-17-1924
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-seq Reveals a Subpopulation of Prostate Cancer Cells with Enhanced Cell-Cycle–Related Transcription and Attenuated Androgen Response

Abstract: Increasing evidence suggests the presence of minor cell subpopulations in prostate cancer that are androgen independent and poised for selection as dominant clones after androgen deprivation therapy. In this study, we investigated this phenomenon by stratifying cell subpopulations based on transcriptome profiling of 144 single LNCaP prostate cancer cells treated or untreated with androgen after cell-cycle synchronization. Model-based clustering of 397 differentially expressed genes identified eight potential s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 40 publications
5
89
0
Order By: Relevance
“…Several studies had reported association of interleukin signaling and inflammation to be more prevalent in AA and over‐activation of PI3K/AKT pathway in AA men compared with CA men . Furthermore, we found cell cycle signaling was downregulated in AAs in line with a recent study that reported enhanced cell cycle‐related transcription in specific subpopulation of CA derived PCa cell‐line . Finally, amino‐acid metabolism pathways were observed to be associated with genes upregulated in CA men (MC3), which was in line with previously reported study that showed higher amino acid metabolism in CA derived PCa cell lines treated with androgens …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies had reported association of interleukin signaling and inflammation to be more prevalent in AA and over‐activation of PI3K/AKT pathway in AA men compared with CA men . Furthermore, we found cell cycle signaling was downregulated in AAs in line with a recent study that reported enhanced cell cycle‐related transcription in specific subpopulation of CA derived PCa cell‐line . Finally, amino‐acid metabolism pathways were observed to be associated with genes upregulated in CA men (MC3), which was in line with previously reported study that showed higher amino acid metabolism in CA derived PCa cell lines treated with androgens …”
Section: Discussionsupporting
confidence: 91%
“…Several studies had reported association of interleukin signaling and inflammation to be more prevalent in AA 17,52 and over-activation of PI3K/AKT pathway in AA men compared with CA men. 53 Furthermore, we found cell cycle signaling was downregulated in AAs in line with a recent study that 54 Finally, amino-acid metabolism pathways were observed to be associated with genes upregulated in CA men (MC3), which was in line with previously reported study that showed higher amino acid metabolism in CA derived PCa cell lines treated with androgens. 55 To establish a premise for a larger study in the future, we carried out a pilot RRBS study using a small cohort of PCa tumors derived from AA (three samples) and CA men (three samples).…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are similar to these findings. Furthermore, we found cell cycle signaling was downregulated in AAs whereas a recent study shows enhanced cell cycle related transcription in specific subpopulation of CA derived prostate cancer cell-line [50]. Finally, similar to our observation of amino-acid metabolism to be associated with CA, Putluri et al, 2011 reported higher amino acid metabolism in CA derived prostate cancer cell lines treated with androgens [51].…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, approximately 13% of the samples showed an intermediate subtype with characteristics of both MetA and MetB, and in the validation cohort (Quigley et al, 2018), this was observed in about 14%. In the LNCaP cell line, single-cell sequencing has demonstrated the existence of multiple subclones where some appear similar to MetA, whereas others are more MetB-like with high cell proliferation and reduced androgen dependency (Horning et al, 2018). Collectively, this suggests that the luminal-derived MetA subtype may be able to dedifferentiate in to the more aggressive MetB subtype, possibly driven by altered AR-activity.…”
Section: Discussionmentioning
confidence: 99%